Perkembangan Bahasa Anak Usia Dini 5-6 Tahun Ditnjau dari Aspek Pragmatik - Listiani, Ernawati; Ramdhani, Intan Sari (Al-DYAS, 2023)
The development of language or communication in children is one aspect of the stages of child development which should not escape the attention of educators in general and parents in particular. The acquisition of language by children is the greatest and most amazing human achievement. During their early years, from birth to 6 years old, they never learn languages, let alone vocabulary in particular, but by the end of their early years, the average child has stored more than 14,000 words. From these two examples it is known that from a pragmatic perspective, children also have developmental differences in understanding and using sign language. This research uses a qualitative descriptive research method. The research samples were two girls of the same age, namely 4-5 years. The researchers concluded that early childhood is from 5 to 6 years old and has differences in pragmatics. Therefore, researchers suggest that teachers understand these developmental differences and encourage students according to their development to continue to develop. The purpose of this research is to describe the language learning of children aged 5-6 years in the field and pragmatic language learning of children aged 5-6 years.